Challenges in dengue research: A computational perspective. (5th November 2017) - Lourenço, José; Tennant, Warren; Faria, Nuno R.; Walker, Andrew; Gupta, Sunetra; Recker, Mario
Abstract: The dengue virus is now the most widespread arbovirus affecting human populations, causing significant economic and social impact in South America and South‐East Asia. Increasing urbanization and globalization, coupled with insufficient resources for control, misguided policies or lack of political will, and expansion of its mosquito vectors are some of the reasons why interventions have so far failed to curb this major public health problem. Computational approaches have elucidated on dengue's population dynamics with the aim to provide not only a better understanding of the evolution and epidemiology of the virus but also robust intervention strategies. It is clear, however, that these have been insufficient to address key aspects of dengue's biology, many of which will play a crucial role for the success of future control programmes, including vaccination. Within a multiscale perspective on this biological system, with the aim of linking evolutionary, ecological and epidemiological thinking, as well as to expand on classic modelling assumptions, we here propose, discuss and exemplify a few major computational avenues—real‐time computational analysis of genetic data, phylodynamic modelling frameworks, within‐host model frameworks and GPU‐accelerated computing. We argue that these emerging approaches should offer valuable research opportunities over the coming years, as previously applied and demonstrated in the context of other pathogens.